2020
DOI: 10.3390/biom10030476
|View full text |Cite
|
Sign up to set email alerts
|

Actionable Potentials of Less Frequently Mutated Genes in Colorectal Cancer and Their Roles in Precision Medicine

Abstract: Global statistics have placed colorectal cancer (CRC) as the third most frequently diagnosed cancer and the fourth principal cause of cancer-related deaths worldwide. Improving survival for CRC is as important as early detection. Personalized medicine is important in maximizing an individual’s treatment success and minimizing the risk of adverse reactions. Approaches in achieving personalized therapy in CRC have included analyses of specific genes with its clinical implications. Tumour genotyping via next-gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 137 publications
(191 reference statements)
0
3
0
Order By: Relevance
“…Previously, studies had proven implementation of biomarkers from blood as a non-invasive method for CRC screening, particularly during its early stages (stage I or premalignant stage) [ 63 , 64 , 65 , 66 , 67 ]. Examples of the markers evaluated were (1) proteins (hemoglobin) [ 68 , 69 , 70 , 71 ]; (2) deoxyribonucleic acid/DNA from intact cells or blood circulation (including methylation markers) [ 72 , 73 , 74 , 75 , 76 , 77 ]; (3) ribonucleic acid/RNA (messenger RNA, non-coding RNA and microRNA) [ 78 , 79 , 80 , 81 ]; (4) genes (mutation) [ 82 , 83 ]; and (5) low molecular weight metabolites (volatile organic compounds) [ 84 ]. Since the approval of first liquid biopsy-based test by the Food and Drug Administration (FDA) in 2016, numerous blood-based detection methods have been the focus of CRC screening to overcome the above-mentioned difficulties in traditional tissue biopsy testing [ 85 , 86 , 87 ].…”
Section: Necessity Of Liquid Biopsy Specimens In Msi Testingmentioning
confidence: 99%
“…Previously, studies had proven implementation of biomarkers from blood as a non-invasive method for CRC screening, particularly during its early stages (stage I or premalignant stage) [ 63 , 64 , 65 , 66 , 67 ]. Examples of the markers evaluated were (1) proteins (hemoglobin) [ 68 , 69 , 70 , 71 ]; (2) deoxyribonucleic acid/DNA from intact cells or blood circulation (including methylation markers) [ 72 , 73 , 74 , 75 , 76 , 77 ]; (3) ribonucleic acid/RNA (messenger RNA, non-coding RNA and microRNA) [ 78 , 79 , 80 , 81 ]; (4) genes (mutation) [ 82 , 83 ]; and (5) low molecular weight metabolites (volatile organic compounds) [ 84 ]. Since the approval of first liquid biopsy-based test by the Food and Drug Administration (FDA) in 2016, numerous blood-based detection methods have been the focus of CRC screening to overcome the above-mentioned difficulties in traditional tissue biopsy testing [ 85 , 86 , 87 ].…”
Section: Necessity Of Liquid Biopsy Specimens In Msi Testingmentioning
confidence: 99%
“…A study on immunohistochemical staining for metastatic colorectal cancer found that patients with a high expression level of c-MYC had a significantly lower progression-free survival time and overall survival than those with reduced c-MYC expression (Strippoli et al, 2020). In summary, these findings indicate that the uncertain role of MYC function warrants further investigation (Yunos et al, 2020).…”
Section: Discussionmentioning
confidence: 87%
“…Despite this fact and the relatively small size of our cohort, the spectrum of CNVs observed in our study was coincident with previous reports. Thus, ERRB2, MET, or EGFR amplifications were frequently found in CRC while FGFR1 and EGFR CNVs were present in a small but significant percentage of lung tumors [17][18][19][20].…”
Section: Discussionmentioning
confidence: 99%